2019
DOI: 10.3934/eect.2019005
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation in flows of asymmetrically interacting particles: Peristaltic pedestrian dynamics as a case study

Abstract: The influence of asymmetry in the coupling between repulsive particles is studied. A prominent example is the social force model for pedestrian dynamics in a long corridor where the asymmetry leads to anisotropy in the repulsion such that pedestrians in front, i.e., in walking direction, have a bigger influence on the pedestrian behavior than those behind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…considering the perception of the environment 39 or asymmetric interactions. 59 However, the modeling approach of a different variety of emotional states by a variable modified by interactions still appears to be an open problem which is tackled in Sec. 4 of our paper.…”
Section: Microscopic (Individual-based) Scalementioning
confidence: 99%
“…considering the perception of the environment 39 or asymmetric interactions. 59 However, the modeling approach of a different variety of emotional states by a variable modified by interactions still appears to be an open problem which is tackled in Sec. 4 of our paper.…”
Section: Microscopic (Individual-based) Scalementioning
confidence: 99%
“…Gaididei et al [9] recently reported pattern formation in flows of asymmetrically interacting particles with peristaltic pedestrian dynamics as a case study.…”
Section: Introductionmentioning
confidence: 99%